Taxonomic notes on Mahanarva (Ipiranga) (Hemiptera, Cercopidae) with description of a new species - Paladini, Andressa; Cavichioli, Rodney Ramiro (Zootaxa, 2014)
Mahanarva (Ipiranga) takiyae sp. nov. (Cercopidae) is described and illustrated from Brazil. This new species can be distinguished from other known species in the genus by the tegmen with three rounded yellow spots and the shape of the paramere. Mahanarva (Mahanarva) rubripennis is transferred to the subgenus Mahanarva (Ipiranga).